On the Importance of Intraindividual Variability in Cognitive Development - Anik de Ribaupierre; Thierry Lecerf (Journal of Intelligence, 2018)
Developmental cognitive psychology (as well as cognitive psychology in general) has a long-standing tradition to ignore all variations other than age, as if individual variations were only measurement error or noise[...]